Distance matters: mobilities and the politics of distance. Issue 4 (4th July 2018) - Handel, Ariel
Abstract: Distance constitutes one of the foundations of geographical discourse, and yet it is among the least discussed of these foundations. Rather than contemplating distance as an explanatory tool, the paper takes distance itself, as well as its development and implications, as requiring explanation in their own right. It looks at the role played by definitions and measurements of distance in the production of territory and private property in land; in the governing of moving bodies; and in the phenomenological and affective design of space. The paper's main argument is that distance should be de-constructed and re-politicized by being brought back into the field of mobilities.